Research fronts on Vitiligo, a Scopus-based bibliometric view - Vega Almeida, Rosa Lidia; Arencibia Jorge, Ricardo (Revista Cubana de Información en Ciencias de la Salud, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]-->Bibliometrics is frequently used to analyze the structural evolution of research fields, especially in biomedical areas. This paper provides a macrostructure of scientific research on Vitiligo during the last fifty years using bibliometric methods. Data were collected from Scopus. A total of 6109 articles related to Vitiligo were processed. Specialized terms based on the structure of the US National Library of Medicine’s Medical Subject Headings (MeSH) Thesaurus were analyzed. A structural approach using terms co-ocurrence analysis was developed. The analysis of hyerarchical clusters was used to identify the research macrostructure by applying the CONCOR (CONvergence of iterated CORrelations) algorithm. The world scientific output on Vitiligo experienced an exponential growth during the last fifty years. Structural analysis revealed eight research areas divided in two blocks. First, an experimental block covering the study of Vitiligo, its relationship with cancer and other autoimmunological disorders, its pathophysiology and pathogenesis; and second, a clinical block involving different therapeutical assessments, incidence and prevalence of the disease. The applied methodology offers a valid tool for description and classification of different biomedical knowledge domains. It is also possible to obtain a domain macrostructure, which can be further validated through literature reviews.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->